Wwc2 Is a Novel Cell Division Regulator During Preimplantation Mouse Embryo Lineage Formation and Oogenesis - Virnicchi, Giorgio; Bora, Pablo; Gahurova, Lenka; Šušor, Andrej; Bruce, Alexander W. (Frontiers in Cell and Developmental Biology, 2020)
Formation of the hatching mouse blastocyst marks the end of preimplantation development, whereby previous cell cleavages culminate in the formation of three distinct cell lineages (trophectoderm, primitive endoderm and epiblast). We report that dysregulated expression of Wwc2, a genetic paralog of Kibra/Wwc1 (a known activator of Hippo-signalling, a key pathway during preimplantation development), is specifically associated with cell autonomous deficits in embryo cell number and cell division abnormalities. Division phenotypes are also observed during mouse oocyte meiotic maturation, as Wwc2 dysregulation blocks progression to the stage of meiosis II metaphase (MII) arrest and is associated with spindle defects and failed Aurora-A kinase (AURKA) activation. Oocyte and embryo cell division defects, each occurring in the absence of centrosomes, are fully reversible by expression of recombinant HA-epitope tagged WWC2, restoring activated oocyte AURKA levels. Additionally, clonal embryonic dysregulation implicates Wwc2 in maintaining the pluripotent epiblast lineage. Thus, Wwc2 is a novel regulator of meiotic and early mitotic cell divisions, and mouse blastocyst cell fate.